Final Income Tax Article 4 paragraph 2 on Interest on Customer Deposits and Savings - Imron Burhan; Mahardian Hersanti Paramita; Rizkyana Agand (Income Journal: Accounting, Management and Economic Research, 2022)
The purpose of this study is to determine the application of Final Income Article 4 clause 2 on interest deposit and savings customers at PT Bank Tabungan Negara (Persero) Branch Panakkukang Makassar.The research method used is descriptive quantitative method. The results showed that withholding of Income Tax Article 4 clause 2 shall be on the interest earned one month multiplied by the prevailing tax rate of 20%. The withholding of withholding tax is made via e-Billing no later than the 10th of the following month after the tax period has expired. Reporting is done no later than the 20th of the following month after the tax period ends. Based on this research, it is concluded that the deduction, deposit, and reporting of Income Tax Article 4, clause 2 on interest deposit and savings of customers at PT Bank Tabungan Negara (Persero) Panakkukang Branch Office Makassar is in accordance with applicable tax laws